2017
DOI: 10.1002/2016jd026424
|View full text |Cite
|
Sign up to set email alerts
|

Why was the arid and semiarid northwest China getting wetter in the recent decades?

Abstract: The arid and semiarid northwest China has experienced a significant wetting trend in summer during 1961–2010, but the reasons remain ambiguous. In this study, moisture budget analysis is employed to quantify the contributions of different factors to the wetting trend. The results show that more than 50% of the increasing precipitation is balanced by the increased evaporation. The convergence of moisture flux (the sum of horizontal moisture advection and wind convergence terms) has a significant positive contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
146
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(180 citation statements)
references
References 79 publications
17
146
1
Order By: Relevance
“…On average, the mean trend of the stations in ASRC is 0.06 events decade −1 . This finding agrees with the increasing trend in the convergence of water flux (the sum of horizontal advection and wind convergence terms) over Northwest China during the past decades (Peng and Zhou, ). On the one hand, the increased downward longwave radiation in this area favors the evaporation and increases the atmospheric moisture; on the other hand, central Asia is covered by an anomalous cyclone and horizontal vorticity advection, thereby leading to a wetting tendency (Peng and Zhou, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, the mean trend of the stations in ASRC is 0.06 events decade −1 . This finding agrees with the increasing trend in the convergence of water flux (the sum of horizontal advection and wind convergence terms) over Northwest China during the past decades (Peng and Zhou, ). On the one hand, the increased downward longwave radiation in this area favors the evaporation and increases the atmospheric moisture; on the other hand, central Asia is covered by an anomalous cyclone and horizontal vorticity advection, thereby leading to a wetting tendency (Peng and Zhou, ).…”
Section: Resultsmentioning
confidence: 99%
“…As suggested by previous studies (Peng and Zhou, ; Wang et al ., ; Liu et al ., ), Northwest China experienced a wetting trend during the past decades. Our analysis confirmed this trend by showing that most areas of ASRC experience a wetter summer climate.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…The aggregation according to precipitation characteristics may lead to attribution of changes to anthropogenic forcing even be robust for smaller areas causing robustness of trends in extreme precipitation for dry regions (Donat et al, ). For the precipitation increase in dry regions of China, previous studies have shown that the changes in moisture and circulation have simultaneous positive contributions to the wetting trend in dry regions (Huang et al, ; Li, Chen, et al, ; Peng & Zhou, ). The thermodynamic contribution to the wetting trend is also induced by the increased specific humidity, which is associated with enhanced evaporation, and the dynamic contribution is dominated by an anomalous cyclone over central Asia (Peng & Zhou, ).…”
Section: Discussionmentioning
confidence: 98%
“…Precipitation and the frequency of extreme precipitation have increased in the NTM at a rate of 11.3% annually (He et al, 2003). Other areas in the Central Asia arid area have experienced slight decreases in average annual precipitation (Gessner et al, 2013;Lioubimtseva & Henebry, 2009) but a significant increasing trend in summer at a rate of 20.78% (Gessner et al, 2013;Lioubimtseva & Henebry, 2009;Peng et al, 2018;Peng & Zhou, 2017). Horton et al found that the dynamic exchange of heat and water to regional climate change is largely dependent on or potentially related to land cover change processes and land management measures (Horton et al, 2015;Qu et al, 2013;Y Zhou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%